Penguatan Karakter Siswa Melalui Pendidikan Islam Integratif (Studi Kasus di Sekolah Dasar Islam Terpadu (IT) Utsman Bin Affan Dasan Lekong - Ansori, Surya Bayu (khatulistiwa, 2024)
The aim of the research carried out was to determine efforts to strengthen student character through Integrative Islamic Education at the Utsman Bin Affan Dasan Lekong Integrated Islamic Elementary School. The research focus was on efforts to strengthen student character through Integrative Islamic Education. The type of research was descriptive qualitative research using a phenomenological approach. data using observation, interviews and documentation techniques and drawing conclusions. The results of the research show that efforts to strengthen student character at the Utsman Bin Affan Integrated Islamic Basic School were carried out through : 1. Preparation of an Integrated Curriculum. 2. Integration of Learning Themes: Learning materials in various general subjects can be linked to the values and teachings of the Islamic religion. 3. Use of Religious Content in Learning 4. Extracurricular Activities with Religious Content.